Governance of global vessel-source marine oil spills: Characteristics and refreshed strategies. (1st November 2021) - Zhang, Weipan; Li, Chenxuan; Chen, Jihong; Wan, Zheng; Shu, Yaqing; Song, Lan; Xu, Lang; Di, Zhongjie
Abstract: With the rapid development of the international shipping industry, global shipping is getting increasingly frequent and vessel-source oil pollution has become one of the significant contributors to marine environmental pollution. As a special method of oil transportation, oil tankers will do more harm if they have oil spills. The marine pollution caused by ship oil spills around the world has become an increasingly prominent concern of the international community. This paper approaches the subject from beforehand prevention, in-process response, ex-post handling, and comprehensive governance aspects. After analyzing the evolution and the characteristics of the vessel-source oil pollution governance policies worldwide, this paper identifies four crucial issues which include defects in oil tankers' fire and explosion prevention technologies, emergency response systems in oil spills, compensation mechanisms for oil pollution damage, and human factors and ship registry system governance. It then proposes strategy to improve the governance of vessel-source oil pollution, in particular refining the fire and explosion prevention technology for oil tankers, enhancing the oil spill emergency response, perfecting the oil pollution compensation system, paying more attention to the human factor, and advancing the management of flags of convenience. In the final section, this paper points out the future directions of research. The aim of this article is providing a systematic and scientific reference for government departments and concerned organizations, and so that they could take actions to tackle global vessel-source oil pollution. Graphical abstract: Image 1 Highlights: Vessel-source oil spills have adverse effects on marine environment. Evolution characteristics of oil spill governance are analyzed. Existing problems of oil spill governance are diagnosed. Future governance directions for oil spills are provided.